KAJIAN LITERATUR: INTERVENSI MICRONUTRIENT VITAMIN, MINERAL, COLD LIVER OIL, FISH OIL DAN ZAT BESI TERHADAP PERKEMBANGAN KOGNITIF ANAK - Aurora, Wahyu Indah Dewi (Scientific Of Environmental Health and Diseases, 2022)
ABSTRACTIntroduction: The effect of nutrition on the cognitive function of the brain is highly dependent on the nutrients involvedin the brain maturation process. The effects of these nutrients on brain structure and function may occur over a shortperiod of time, while others may not be apparent until maximal maturation. Optimizing brain development and cognitivefunction has a very long impact on individuals and society. The purpose of this literature review is to determine theimpact of micronutrient interventions, vitamins, minerals, cold liver oil, fish oil and iron on children's cognitivedevelopment.Method: The method used in this research is the Literature Review. The data sources are articles in journalsdownloaded from EBSCOhost, Science Direct, Lancet, ProQuest, Gale, E-perpusnas, Pubmed, Google scholar andWiley Online Library.Results: The study using the vitamin supplement intervention resulted in a significant difference in all test results (UNITtest, executive function and motor function) with children who received the intervention. Research by giving cod liveroil supplements LCPUFAs states that there is a positive effect shown on children's cognitive processes. Researchconducted by giving Supplementary Fish oil capsules showed a positive effect shown from pregnancy given fish oilintervention on eye and hand coordination.Conclusion: The provision of micronutrients such as vitamins, minerals, cold liver oil, fish oil and iron has a significanteffect on children's cognitive development when viewed from various sources.Keywords: Micronutrients intervention, Cognitif DevelopmentABSTRAKPendahuluan: Efek nutrisi pada fungsi kognitif otak sangat tergantung pada nutrisi yang terlibat pada prosespematangan otak. Efek nutrisi ini pada struktur dan fungsi otak dapat terjadi pada jangka waktu pendek, sementarayang lain mungkin tidak terlihat sampai pematangan maksimal. Pengoptimalan perkembangan otak dan fungsi kognitiftersebut memiliki dampak yang sangat panjang bagi individu dan masyarakat. Tujuan kajian literatur ini adalah untukmengetahui dampak intervensi micronutrient vitamin, mineral, cold liver oil, fish oil dan zat besi terhadap perkembangankognitif anak.Metode: Metode Yang Digunakan pada penelitian ini adalah Literatur Review. Sumber datanya adalah artikel di dalamjurnal yang diunduh dari EBSCOhost, Science Direct, Lancet, ProQuest, Gale, E-perpusnas, Pubmed, Google scholardan Wiley Online Library. Hasil: Penelitian dengan memberkan intervensi suplemen vitamin hasilnya adalah adanya perbedaan yang signifikandi semua hasil test (test UNIT, fungsi eksekutif dan fungsi motoric) dengan anak-anak yang menerima intervensitersebut. Peneltian dengan memberikan suplemen cod liver oil LCPUFAs menyebutkan bahwa ada efek yang positifyang ditunjukkan pada proses kognitif anak. Penelitian yang dilakukan dengan memberikan Suplement Fish oil capsulemenunjukkan efek yang positif yang ditunjukkan dari kehamilan yang diberikan intervensi fish oil terhadap mata dankoordinasi tangan.Kesimpulan: Pemberian micronutrient seperti vitamin, mineral, cold liver oil, fish oil dan zat besi memiliki pengaruhyang signifikan terhadap perkembangan kognitif anak jika dilihat dari berbagai sumber.Kata Kunci: Intervensi Mikronutrient, Perkembangan kognitif anak